Surface Modification of Screen-Printed Carbon Electrode through Oxygen Plasma to Enhance Biosensor Sensitivity - Shuto Osaki; Masato Saito; Hidenori Nagai; Eiichi Tamiya (Biosensors, 2024)
The screen-printed carbon electrode (SPCE) is a useful technology that has been widely used in the practical application of biosensors oriented to point-of-care testing (POCT) due to its characteristics of cost-effectiveness, disposability, miniaturization, wide potential window, and simple electrode design. Compared with gold or platinum electrodes, surface modification is difficult because the carbon surface is chemically or physically stable. Oxygen plasma (O2) can easily produce carboxyl groups on the carbon surface, which act as scaffolds for covalent bonds. However, the effect of O2-plasma treatment on electrode performance remains to be investigated from an electrochemical perspective, and sensor performance can be improved by clarifying the surface conditions of plasma-treated biosensors. In this research, we compared antibody modification by plasma treatment and physical adsorption, using our novel immunosensor based on gold nanoparticles (AuNPs). Consequently, the O2-plasma treatment produced carboxyl groups on the electrode surface that changed the electrochemical properties owing to electrostatic interactions. In this study, we compared the following four cases of SPCE modification: O2-plasma-treated electrode/covalent-bonded antibody (a); O2-plasma-treated electrode/physical adsorbed antibody (b); bare electrode/covalent-bonded antibody (c); and bare electrode/physical absorbed antibody (d). The limits of detection (LOD) were 0.50 ng/mL (a), 9.7 ng/mL (b), 0.54 ng/mL (c), and 1.2 ng/mL (d). The slopes of the linear response range were 0.039, 0.029, 0.014, and 0.022. The LOD of (a) was 2.4 times higher than the conventional condition (d), The slope of (a) showed higher sensitivity than other cases (b~d). This is because the plasma treatment generated many carboxyl groups and increased the number of antibody adsorption sites. In summary, the O2-plasma treatment was found to modify the electrode surface conditions and improve the amount of antibody modifications. In the future, O2-plasma treatment could be used as a simple method for modifying various molecular recognition elements on printed carbon electrodes.